Peru and its neighbors: fundaments for a peace culture - González Riesle, Álvaro (2021)
Aiming at grounding the design of a Peace Culture strategy for the relationships among Peru and its bordering countries, a research was developed in 409 Education students: 159 from a private and 250 from a public university. Relationships among six independent variables: Dogmatism (DOG), Right-Wing Authoritarianism (RWA), Social Domination (SDO), Machiavellianism (MAQ), Nationalism (NAC) and Patriotism (PAT) with five dependent variables (perception on attitudes towards Peru in the areas of: Courtesy, Non-Probability of War, Trustworthiness, Solidarity and Cooperativeness-Conflictiveness) as perceived in five bordering countries: Ecuador, Colombia, Brazil, Bolivia, and Chile, were assessed. Six Likert-type attitude questionnaires and a Semantic Differential (DS) were applied. Descriptive and correlational analysis were developed and semantic distance matrices were structured among the above mentioned countries. The results only partially confirm the proposed hypothesis. The independent variables did not integrate an acceptable predictive model. Only the RWA appears as a predictor for the perceptions on Non-Probability of War with Chile, and Patriotism as predictor for the perceptions on Courtesy,Non-Probability of War ,Trustworthiness, Solidarity and Cooperativeness-Conflictiveness in the case of Bolivia. As far as the Conservative Ideology (IC) was concerned, a direct relationship between PAT and the IC’s RWA component, and a reverse relation with SDO were registered. The attitudes towards Peru’s perceptions related to Ecuador, Colombia, Brazil and Bolivia accumulated themselves nearer to the favorable pole of Semantic Differential (DS) ,and the corresponding to Chile were located nearer to the unfavorable pole. On the basis of these findings, recommendations were offered on Peace Research and Education strategies.